(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background: Secondary glaucoma is found in 18% to 38% of patients with uveitis, and is one of the most severe uveitic complications. The glaucomatous process is characterized by the progressive optic nerve neuropathy. The lack of efficacy of conventional neuroprotective approaches urged us to search for novel medications capable of stabilizing glaucoma. Purpose: To investigate the efficacy of neuroprotective treatment with pyrimidine nucleotides for secondary uveitic glaucoma. Materials and Methods: Patients with secondary uveitic glaucoma were divided into the study group (23 patients; 23 eyes) and the control group (21 patients; 21 eyes). The multicomponent neuroprotective treatment of the study group (but not of the control group) included a direct neuroprotector, Nucleo CMP Forte® drug containing two pyrimidine nucleotides, cytidine 5’-monophosphate and uridine 5’- triphosphate. The group received 2 ml of the drug intramuscularly daily for 10 days, and, thereafter, 2 capsules orally twice daily for 20 days. Each patient underwent visual acuity measurement and perimetry. In addition, phosphene threshold current (PTC) and critical frequency of phosphene (CFP) were determined. Results: Although no improvements in functional characteristics of the visual system were observed in the control group, the use of the pyrimidine nucleotide-containing drug as a component of therapy for uveitic glaucoma contributed to a 39% improvement in visual acuity, 17% increase in total visual field, 22% decrease in PTC, and 23% increase in CFP compared with baseline. Our long-term findings evidence that glaucoma was stabilized with neuroprotective therapy including, in particular, Nucleo CMP Forte, with generally maintained peripapillary RNFL thickness. Conclusion: The use of the pyrimidine nucleotide-containing drug as a component of therapy for uveitic glaucoma promoted an improvement in visual function and contributed to stabilization of glaucoma over 6-8 months.